Influencia de la Cultura Organizacional en la Calidad de atención del servicio del personal Administrativo de la Universidad Nacional de San Martín – Tarapoto - Tuesta Pinedo, Jorge Armando (2016)
The traditional notion of the employment has evolved significantly in the last years, specially in the most developed companies. The diversity and the flexibility opposite to the standardization, the identification of the worker with his institution with elements that have changed deeply the priorities and the management of the field of the human resources. The persons are the central element of the Public administration, that´s why that any process of transformation must settle down on the advanced management of its human resources. The public sector must manage its human resources of an efficient way because it has the tools to do it, because there exists the juridical support that allows it and because it is strictly necessary to attack a real process of change. This work of investigation " INFLUENCE OF THE ORGANIZATIONAL CULTURE IN THE QUALITY OF ATTENTION OF THE SERVICE OF THE ADMINISTRATIVE PERSONNEL FROM THE NATIONAL UNIVERSITY OF SAN MARTIN - TARAPOTO ", It proposes the practice of the quality in the attention to the service as a valuable tool of business management in such way that it makes the constant improvement about the treatment of the personnel of the UNSM - T with their users. The study diagnoses and describes the quality of attention that impart the administrative servants give in our first house of top studies, the same one that was realized by means of the summary of information obtained so much to the interior of the university, as well as in the exterior of the same one, there has been realized the analysis and interpretation of the principal indicators to the management and there decided the existence of a good culture organizational as conditioning for the existence of a good quality of attention. In that way there is still much for improving, to correct and only workers, authorities and students are the entities in charge of the great transformation and to achieve such a longed Accreditation.